2014
DOI: 10.1038/leu.2014.84
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β upregulates CD70 expression and induces exhaustion of effector memory T cells in B-cell non-Hodgkin’s lymphoma

Abstract: Transforming growth factor beta (TGF-β) plays an important role in mediating T-cell suppression in B-cell non-Hodgkin lymphoma (NHL). However, the underlying mechanism responsible for TGF-β-mediated inhibition of effector memory T (Tm) cells is largely unknown. As reported here, we show that exhaustion is a major mechanism by which TGF-β inhibits Tm cells, and TGF-β mediated exhaustion is associated with upregulation of CD70. We found that TGF-β upregulates CD70 expression on effector Tm cells while it prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 52 publications
3
96
0
1
Order By: Relevance
“…studies have found and proposed a direct link between circulating levels of TGF-β and the risk of NHL (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…studies have found and proposed a direct link between circulating levels of TGF-β and the risk of NHL (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…67,68 These functional defects coincide with an increased expression of CD244, CD160, and PD-1 on CLL-derived T cells, a phenotype that is similar to the phenotype of exhausted T cells in chronic viral infections. 69 Targeting these immune checkpoints has been a new approach in the treatment of malignant lymphomas, and is now being explored in large clinical studies. 70 Also relevant to anti-tumor immune responses are immune cells belonging to the innate immune systems, such as NK cells and monocytes/macrophages.…”
Section: Cancer-induced Immune-suppression; Cancer Progression and Inmentioning
confidence: 99%
“…Thus, TGFB1 polymorphism effect in HM development might be explained by the impairment in TGFβ1 secretion and the consequent decrement of cytostatic effects exerted by this cytokine directly in hematologic cells. It would also be interesting to evaluate a possible effect of this polymorphism during disease course, where TGFβ1 effects in anti-neoplastic immunological responses play important role (Yang et al 2013;Yang et al 2014), an issue that could not be assessed in this study due to limited and heterogeneous sample.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it has been shown that in non-Hodgkin lymphoma, malignant B-cells are capable of secreting TGFβ1 and induce T-cell exhaustion (Yang et al 2014) and differentiation into Tregs, creating an immunopermissive microenvironment (Yang et al 2013). Indicating Tregs importance on the pathogenesis of HM, Ishida et al (Ishida et al 2006) demonstrated that Hodgkin Lymphoma cells attracted Tregs to affected lymph nodes.…”
Section: Resultsmentioning
confidence: 99%